Behind the Mask: A graphical autobiography of life and labor in the oil sands - Roopalakshmi Velu; Rajasekaran V (Humanities & Social Sciences Communications)
Abstract This article examines the multifaceted realities of the Oil Sands industry in Kate Beaton’s graphic memoir Ducks: Two Years in the Oil Sands (2022). The visual-verbal narrative of Ducks illustrates how the oil sands serve not only as a backdrop but also as a metaphor for societal structures that marginalize women and perpetuate broader issues such as sexism and mental health neglect. Focusing on the lived experiences of laborers, women in particular, the article engages with the themes of sexism, labor, and environmental degradation endemic to oil boomtowns. Utilizing Rebecca Scherr’s concept of grounding in graphic novels, the article further inspects the intricate relationship between human subjects and their spatial context, revealing how physical environments reflect and reinforce gendered dynamics. Through close inspection of Beaton’s narrative, this article underscores the often-overlooked intersection of environmental degradation and individual suffering, positing that grounding fortifies the narrative’s thematic depth. Ultimately, this paper advocates for a heightened awareness of the intertwined socio-environmental challenges intrinsic to the oil industry, positioning the call for conscientious engagement as paramount in addressing the complexities of contemporary existence.